Successful treatment of left main shock syndrome induced by thrombosed coronary artery dissection: A case report. Issue 17 (April 2018) - Bai, Xiaojun; Zhang, Weiping; Yuan, Zuyi
Abstract: Rationale: Left main shock syndrome (LMSS) induced by thrombosed coronary artery dissection is very rare and has a fatal prognosis. Optimal treatment strategy includes early reperfusion and hemodynamic support to prevent cardiogenic shock. However, it involves the extension of technical difficulties under different conditions. Patient concerns: A 49-year-old woman developed symptoms of left main shock syndrome. The main clinical manifestations were retrosternal pain radiating to his back and left shoulder, heavy sweating, palpitation and brachypnea. Diagnoses: Acute anterioseptal myocardial infarction (Killip Class IV) with cardiogenic shock and arrhythmia including ventricular tachycardia and idionodal rhythm, and coronary artery dissection. Interventions: A thrombus aspiration procedure was performed for the establishment of coronary flow under intra-aortic balloon pumping (IABP) support. Her coronary angiographic finding demonstrated a dissection in the mid-distal segment of the left main coronary artery where a sirolimus-eluting stent was deployed. Then, the veno-arterial extra-corporal membrane oxygenation (ECMO) was placed to improve severe cardiac dysfunction and end-organ failure. Outcomes: The patient had a good outcome without active symptoms. Lessons: Thrombosis on the basis of coronary dissection is a very rare cause of LMSS. Successful team treatments, including the prompt thrombus aspiration and stent repair of artery dissection, potent IABP and ECMO support are important to improve the clinical outcome.